2016
DOI: 10.17576/pengurusan-2016-47-01
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Needs-Supplies Fit and Job Satisfaction in Predicting Employee Engagement

Abstract: penawaran-keperluan; kepuasan kerja; self-in-role view; Malaysia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
(113 reference statements)
2
7
0
Order By: Relevance
“…First, in line with earlier research showing internal consistency reliability of the JES ranged from 0.88 to 0.96 (e.g., Alfes et al, 2012;Basit & Arshad, 2016;Byrne et al, 2016;Chen et al, 2014;He et al, 2013;Rich et al, 2010;Shuck et al, 2014), the JES in the present study showed excellent internal consistency reliabilities well above the cutoff criteria of 0.70 (Nunnally & Bernstein, 1994) for both Pakistan (α = 0.97) and Malaysia (α = 0.95).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…First, in line with earlier research showing internal consistency reliability of the JES ranged from 0.88 to 0.96 (e.g., Alfes et al, 2012;Basit & Arshad, 2016;Byrne et al, 2016;Chen et al, 2014;He et al, 2013;Rich et al, 2010;Shuck et al, 2014), the JES in the present study showed excellent internal consistency reliabilities well above the cutoff criteria of 0.70 (Nunnally & Bernstein, 1994) for both Pakistan (α = 0.97) and Malaysia (α = 0.95).…”
Section: Discussionsupporting
confidence: 90%
“…Earlier studies utilizing the JES on Western samples have shown good psychometric properties of this scale and supported its three-factor structure (e.g., Alfes, Shantz, Truss, & Soane, 2012;Basit & Arshad, 2016;Byrne, Peters, & Weston, 2016;Chen, Yen, & Tsai, 2014;He, Zhu, & Zheng, 2014;Rich et al, 2010;Shuck, Twyford, Reio, & Shuck, 2014). However, application of the JES in Asia is relatively limited.…”
Section: Introductionmentioning
confidence: 86%
“…As such, this study assumes that N-S fit is critically crucial for TGs who perceive money as their key motivation during COVID-19 to sustain a living. N-S fit could mediate the relations between psychological meaningfulness and employee engagement, as well as to improve employee job satisfaction by establishing employee feelings of meaningfulness and safety (Basit & Arshad, 2016). Employees with high job satisfaction feel that the organization is concerned to meeting their needs which will encourage them to give back by improving their job engagement at work.…”
Section: The Relationship Between P-o Fit P-j Fit and P-g Fit With 'J...mentioning
confidence: 99%
“…In addition, a continuous effort of human resource development policies will assist organizations to improve their employer branding, which eventually improves employees' commitment and motivation (Lee & Bruvold, 2003). Furthermore, N-S fit will also improve employee engagement and job satisfaction (Basit & Arshad, 2016). Therefore, it is important to strengthen N-S fit and TGs 'career' orientation to improve their MoW.…”
Section: The Relationship Between P-o Fit P-j Fit and P-g Fit With 'C...mentioning
confidence: 99%
“…Resources and support, commonly termed 'perceived organisational support', refer to anything provided by organisations for employees to perform their work tasks (Abas, Omar, Halim & Hafiz, 2016). Past studies indicate that organisational support has positive impact on employees (Kim, Eisenberger, & Baik, 2016;Basit & Arshad, 2016). Resources and support can be anything perceived by employees that assist them in the achievement of their work goals (Halbesleben, Neveu, Paustian-Underdahl, & Westman, 2014).…”
Section: H3:career Awareness and Interests Have Significant Impact On...mentioning
confidence: 99%